THE CORE STABILITY EXERCISE MENINGKATKAN KESEIMBANGAN DINAMIS LANJUT USIA DI BANJAR BEBENGAN, DESA TANGEB, KECAMATAN MENGWI, KABUPATEN BADUNG - I.A. Astiti Suadnyana; Sutha Nurmawan; I Made Muliarta (Majalah Ilmiah Fisioterapi Indonesia, 2015)
Balance disorder is a common problem that found among senior citizens. Those problemswould arise from a balance disorder is an increased risk of falls among senior citizens. Thepurpose of this study was to determine the effectiveness of core stability exercise inincreasing the dynamic balance among senior citizens. Experimental research was donewith randomized pre and post test control group design. Sample of 24 subjects were dividedinto two groups, each group consisting of 12 subjects. The first group as a control groupwith conventional conditions, while the second group as the treatment group with corestability exercise intervention. Dynamic balance was measured using TUGT (Times Up GoTest) and data analysis using independent t-test the mean difference obtained in the controlgroup with conventional condition 0.484 ± 0.431 and the mean difference between thetreatment groups with core stability exercise intervention 3.611 ± 0.918, the obtained valueof p = 0.000 (p <0.05). In conclusion, there was a significant difference in the dynamicbalance between the control group and the treatment group, in which the treatment groupwith core stability exercise intervention can significantly improve the dynamic balanceamong senior citizens.